Congenital absence of uterine cervix - Lakshmy, Selvaraj Ravi; Rose, Nity (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Cervical agenesis or dysgenesis is an extremely rare congenital anomaly. Patients with congenital absence of the cervix present with primary amenorrhea and infertility. Though it poses a diagnostic challenge to the clinician, correct diagnosis prior to surgery is possible with the help of ultrasound. Early diagnosis offers significant advantages in patient care and effective presurgical planning. This case report reviews two cases of cervical agenesis diagnosed with the help of ultrasound and later confirmed with the help of MRI. Ultrasonography is the modality of choice to define the internal genital anatomy and helps us to classify the level of obstruction or aplasia in obstructive uterine anomalies.